PENGARUH SELF EFFICACY DAN CREATIVE THINKING TERHADAP AKTUALISASI DIRI PADA PROGRAM SDGS - Endah Tri Mawarni; Jun Surjanti (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
Countries in the world are developing sustainable development goals. One of the objectives of this program is to realize sustainable education so that students can actualize themselves to face global challenges. This research was conducted to find out how the influence between self-efficacy and creative thinking of the self-actualization of students. The population of this study was a middle and high school teenager in the Surabaya and Sidoarjo region. The number of samples used was 101 people. Sampling techniques use the Accidental Sampling and Purposive Sampling method. Data retrieval techniques use a questionnaire with a Likert scale. Data analyzed using multiple linear regression analysis with the SPSS for Windows version 24. The results of this study, namely 1) Self efficacy has a positive and significant effect on self-actualization 2) Creative Thinking partially has a positive and significant effect on self-actualization 3) Self efficacy and Creative Thinking together can affect self-actualization